(untitled) (Dentika: Dental Journal, 2021)
Tooth extraction is a process of removing teeth from the alveolar bone. In wound healing, fibroblast are very important cells. The main purpose of this study was to determine the effect of mobe leaf 1% and 3% extract gel (Artocarpus lakoocha) on fibroblast proliferation in post extraction tooth socket wound healing. This research used 16 samples of wistar rats, divided into 4 groups, a positive control group, a negative control group and a 1% and 3% mobe leaf extract gel group. The left mandibular incisors were extracted, then 1% and 3% gels of mobe leaf extract were applied on day 1 to day 7. Data analysis was calculated using the Kruskal-Wallis test on clinical data and one way ANOVA test for microscopic. The result of the socket wound healing activity test for a good concentration of mobe leaf extract gel was 3%. This research shows significant resultith p-value of 0.018 (< 0.05) on the closure of the socket wound clinically which means the closure of the wound accelerates because of the mobe leaf 3% extract gel treatment. The distance of fibroblast on microscopically shows significant resultith a p-value of 0.002 (< 0.05), which means that there was an enlargement of the distance fibroblast at the socket wound closure with application of mobe leaf 3% extract gel. From the results of the study it can be concluded that mobe leaf 3% extract gel has the best ability to show acceleration the closure of the socket wound either clinically or microscopically.